Benefits of GLP-1 (Glucagon-Like Peptide 1) Receptor Agonists for Stroke Reduction in Type 2 Diabetes: A Call to Action for Neurologists. Issue 5 (9th March 2022) - Goldenberg, Ronald M.; Cheng, Alice Y.Y.; Fitzpatrick, Tess; Gilbert, Jeremy D.; Verma, Subodh; Hopyan, Julia J.
Abstract : People living with diabetes are at higher risk for stroke and have a poorer prognosis following a stroke event than those without diabetes. Data from cardiovascular outcome trials and meta-analyses indicate that GLP-1RAs (glucagon-like peptide 1 receptor agonists) reduce the risk of stroke in individuals with type 2 diabetes. Accordingly, many guidelines now recommend the addition of GLP-1RAs to ongoing antihyperglycemic regimens to lower the risk of stroke in type 2 diabetes. The current work summarizes evidence supporting the use of GLP-1RAs for stroke reduction in people with type 2 diabetes and offers 2 new resources for neurologists who are considering GLP-1RAs for their patients—a list of frequently asked questions with evidence-based answers on safely initiating and managing GLP-1RAs, and a practical decision-making algorithm to assist in using GLP-1RAs as part of a stroke reduction strategy.